Enhanced Technology for Logistics Courier Delivery Using RFID Label to Minimize Processing Time - Novitasari, Nia; Anwar, Nashirudin (Society of Visual Informatics, 2022)
Courier services have become a sector that has experienced a growth spurt during the Covid-19 pandemic. The soaring growth of courier services is due to e-commerce in Indonesia. Increased people's digital activities show this during the pandemic, including online or online shopping. Data from the Indonesian Ministry of Finance shows that purchase transactions via e-commerce increased 18.1 percent to 98.3 million, with a total transaction value of 9.9 percent to Rp20.7 trillion. Fast and efficient delivery and pick-up of goods is the core operation of courier services. The biggest challenge for courier service providers is how to compete with other companies that offer the same type of service. Service users are increasingly demanding the security and reliability of delivery services so that they can meet the expectations of service users. The expectations of service users used as targets for company achievement are (1) reliability (on time, accuracy, integrity), (2) convenience (collecting units, delivery coverage, operating hours), (3) services, and (4) cost. Based on the activities in courier services, the potential for errors or inefficiencies in processing time is in the pre-delivery activities. In the pre-delivery activity is also the initial activity used to input the data base, collect goods, distribute goods and so on. This research proposes that RFID Label technology can overcome errors and increase process time efficiency in shipping goods on courier services, especially in pre-delivery and delivery activities.